Pendekatan Simulasi Monte Carlo Untuk Pemilihan Alternatif Dengan Decision Tree Pada Nilai Outcome Yang Probabilistik - Winda Nur Cahyo (Teknoin, 2008)
Tree Diagram has been familiarly known as one of the tools used to solve or to make decision forproblems  that  have  some  alternatives  of  solutions.  But  usually  the  outcome  of  the  diagram  aredeterministicly approached. This paper suggested Monte Carlo Simulation to approach the deterministicaspect of outcome to become  probabilistic. But there are some asumtions of the diagram  must be changeto adjust the Monte Carlo Approach.Keywords: Tree Diagram, Monte Carlo Simulation, Decision Analysis.